2018 27th IEEE International Symposium on Robot and Human Interactive Communication (RO-MAN) 2018
DOI: 10.1109/roman.2018.8525672
|View full text |Cite
|
Sign up to set email alerts
|

Do We Really Like Robots that Match our Personality? The Case of Big-Five Traits, Godspeed Scores and Robotic Gestures

Abstract: This work investigates the role of the attraction paradigm-the tendency to associate similarity and attraction in interpersonal relations-in Human-Robot Interaction. The experiment presented here involved 30 human observers who watched and rated 45 robotic gestures in terms of Big-Five personality traits and Godspeed scores. The results show that, for 24 of the 30 observers, there was a statistically significant correlation between the Godspeed scores and the perceived similarity between the robot's personalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…In previous studies the authors published results on the role of personality as a mediation variable between gestures of different energy and spatial extension of a robot [11], the occurrence of a similarity attraction effect for the majority of the observers involved in the experience [12], and the understandability of the gestures displayed [13]. This study shows that changing the way a gesture is displayed is associated, to a statistically significant extend, with changes in the users' perception of those gestures.…”
Section: Introductionmentioning
confidence: 54%
“…In previous studies the authors published results on the role of personality as a mediation variable between gestures of different energy and spatial extension of a robot [11], the occurrence of a similarity attraction effect for the majority of the observers involved in the experience [12], and the understandability of the gestures displayed [13]. This study shows that changing the way a gesture is displayed is associated, to a statistically significant extend, with changes in the users' perception of those gestures.…”
Section: Introductionmentioning
confidence: 54%
“…Several studies have been conducted to investigate the effect of personality similarity on the engagement level of the user during interactions. Craen et al [15] investigated the role of the similarity attraction effect and its relationship with the perceived quality of HRIs based on a comparative analysis between the BFI and Godspeed questionnaires. In the presented experiment, participants were asked to rate 45 robotic gestures from video clips.…”
Section: Similarity Principle In Human-robot Interactionmentioning
confidence: 99%
“…Nonetheless, the research in this area is still fragmented and not properly investigated despite its relevance [42]. Current research has focused on two main aspects of robot personality: (1) the study of the similarity and complementary attraction principle [15,16], and (2) the development of computational models of personality traits based on verbal and non-verbal cues [1]. As very relevant, these two aspects will be investigated in the presented work.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have found several clear relationships: for example, manipulating the amplitude and speed significantly affected users' perception of the Extraversion and Neuroticism of the robot, while the attributed personality also affected users' subjective reactions to the robot (Craenen et al 2018b). In addition, it was found that while the majority of users preferred a robot that they perceived to have a similar personality to their own, a significant minority preferred a robot whose personality was perceived to be different than their own (Craenen et al 2018a).…”
Section: Social Signal Generationmentioning
confidence: 99%